Analisis systematic literature review penguatan pendidik Islam dalam perspektif tafsir, fiqh, dan ilmu sosial prophetic - Herlina Herlina; Arbi Arbi; Syarifuddin Syarifuddin; M. Fahli Zatrahadi; Darmawati Darmawati; Ifdil Ifdil; Istiqomah Istiqomah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
A The approaches of interpretation, fiqih, and prophetic social science can be used to strengthen the quality of Islamic education in educational institutions. Research aims to find out about the strengthening of Islamic educators from the perspectives of Tetris, fiqih, and social science. The research method uses a systematic literature review study. There are 20 articles that meet the quality assessment of 18. 975 with an article-shaped document type. Researchers are using the Dimensions database as a data source. Data analysis uses Nvivo software to obtain more accurate data. Some of the themes discussed based on Nvivo's analysis include increasing understanding of Islamic teachings, increasing critical thinking ability, strengthening students' Islamic identity, increasing the application of Islamic values, and increasing educators' confidence in teaching about Islam. Improving educators' understanding of Islamic teachings, strengthening educators' ability to interpret the Quran and Hadith, and enhancing educators' ability to integrate Islamic values into teaching, more caring and empathic behavior, more critical and analytical understanding, more open and inclusive attitudes, and more creative and interactive teaching. Research results suggest that Islamic educators have a very important role in developing Islamic education in educational institutions. To provide quality instruction, Islamic educators must have a good understanding of the interpretation of the Qur'an, fiqih, and social science. Through this understanding, Islamic educators will be able to provide proper instruction and be relevant to the context of students' lives.